Pharmacognostic Studies on Leaf of Ancistrocladus heyneanus WALL - Naik, Archana (International Journal of Pharmaceutical & Biological Archive, 2014)
Pharmacognostic Studies on Leaf of Ancistrocladus heyneanus WALL